2020
DOI: 10.3390/insects11120875
|View full text |Cite
|
Sign up to set email alerts
|

The Clicking Elateroidea from Chinese Mesozoic Deposits (Insecta, Coleoptera)

Abstract: Recent molecular studies have suggested that the clicking beetle families Elateridae, Eucnemidae, Throscidae, and Cerophytidae evolved in the Jurassic and diversified in the Cretaceous. These studies paid little attention to fossils, using them only as dating tools. The identification of Elateridae fossils is challenging, as external synapomorphies are not known for this family. Elateridae can be identified only as something not belonging to the other related families, all of which have diagnostic synapomorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(60 citation statements)
references
References 29 publications
2
58
0
Order By: Relevance
“…Oberprieler et al [ 98 ] reported a possible elaterid fossil from the Upper Jurassic of Australia. Most recently, Kundrata et al [ 12 ] compiled an updated comprehensive summary of the fossil genera in Elateridae, including their systematic placement and information on the type species, gender, number of species, age range, and relevant bibliography, and Muona et al [ 99 ] revised the clicking Elateroidea from Chinese Mesozoic deposits, with several former click-beetle taxa transferred to Throscidae and Eucnemidae. This study is a follow up to the annotated catalogue of fossil genera in Elateridae [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oberprieler et al [ 98 ] reported a possible elaterid fossil from the Upper Jurassic of Australia. Most recently, Kundrata et al [ 12 ] compiled an updated comprehensive summary of the fossil genera in Elateridae, including their systematic placement and information on the type species, gender, number of species, age range, and relevant bibliography, and Muona et al [ 99 ] revised the clicking Elateroidea from Chinese Mesozoic deposits, with several former click-beetle taxa transferred to Throscidae and Eucnemidae. This study is a follow up to the annotated catalogue of fossil genera in Elateridae [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of Anischiinae fossils with a set of plesiomorphic elateroid features combined with the Anischiinae synapomorphies offered support for the earlier hypothesis [24], and clarified the exact position of Anischiinae within Eucnemidae. The polymorphism of apical elytral excretory punctures in extant species is exceptional, but as stated in Muona and Teräväinen [10], this feature has been lost secondarily in some derived Macraulacini as well.…”
Section: Discussionmentioning
confidence: 90%
“…Chang et al [6] and Muona et al [10] showed that basal lignicolous Eucnemidae diversification had taken place in the Jurassic and the Cretaceous. Here, we demonstrated that Anischiinae were present in the Cretaceous as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations